2016
DOI: 10.1021/acsomega.6b00015
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Binding Peptide Consisting of Four Types of Amino Acid by in Vitro Selection Using cDNA Display

Abstract: RNA–protein interactions have a central role in the living world. In this article, we examined whether primitive peptides (30 residues) consisting of four types of amino acid (Gly, Ala, Asp, and Val) could interact with tRNA as a model of primitive RNAs in the RNA world. By in vitro selection of binding peptides using the cDNA display method, a characteristic peptide was selected from a random peptide library and assayed by electrophoretic mobility shift and pull-down assays. Interestingly, the selected peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…For comparison, Kumachi et al. selected a 30‐residue tRNA‐binding peptide from a four‐amino‐acid code library (using the degenerate codon GNC: Gly, Ala, Asp, Val) but found that only 13 % of all variants (6/46) conformed to their alphabet as determined by sequencing after the selection . Some degree of mutation that leads to undesirable non‐alphabet codons is inevitable during library synthesis and propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, Kumachi et al. selected a 30‐residue tRNA‐binding peptide from a four‐amino‐acid code library (using the degenerate codon GNC: Gly, Ala, Asp, Val) but found that only 13 % of all variants (6/46) conformed to their alphabet as determined by sequencing after the selection . Some degree of mutation that leads to undesirable non‐alphabet codons is inevitable during library synthesis and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to characterise the impact of amino acid composition on the biophysical properties of the reducedalphabet protein variants as a first step to investigating the effect that an evolving, increasingly complex genetic code would have upon protein structure and function. Previous studies have attempted to estimate the function of ancient hypothetical genetic codes, but a major strength of our approach is in the quality of our libraries. Specifically, we designed the libraries to strictly adhere to the reduced alphabets within the randomised regions, with no compromise for nonlibrary amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…S1 ) with a His × 6 tag at C-terminus by PCR. For efficient transcription and translation, T7 promoter, tobacco mosaic virus Ω, and Kozak sequences were attached as 5′-UTR (see Supplementary Table S2 for the sequence) [ 8 ]. The created library (7 × 10 12 molecules at the first round) was transcribed into mRNA, and ligated to our original puromycin linker incorporating fluorescein and biotin (SBP-linker) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The created library (7 × 10 12 molecules at the first round) was transcribed into mRNA, and ligated to our original puromycin linker incorporating fluorescein and biotin (SBP-linker) [ 15 ]. The ligation product was translated in vitro using rabbit reticulocyte lysate, and incubation under high salt concentration was performed to promote mRNA-protein fusion [ 8 ]. Thus-obtained sample was used for EMSA selection.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the abundance of positive and negative amino acids in the environment, both modes of interaction could have been present while experimental data to support such hypothetical modes of interaction are lacking. Importantly, a tRNA-binding peptide composed of only Gly, Ala, Asp and Val was recently selected using cDNA display but the structural mechanism of the binding has not been further characterized (Kumachi et al 2016). To shed more light on the possible mechanism of early protein-RNA interaction, we expressed the most enriched variants from the E and M pools of the CL11 protein domain and characterized them in both uncomplexed and complexed forms.…”
Section: Discussionmentioning
confidence: 99%